2022
DOI: 10.36103/ijas.v53i1.1510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Several Wheat Cultivars in Respond to Different Types of Fertilizers Including Bio-Fertilizer Under Rainfed Conditions

Abstract: The research was conducted during 2018-2019 growing season to study the growth and yield of various wheat cultivars under various methods of fertilizers application including bio-fertilizer under rainfed conditions of two different isohyets conditions. Randomized complete block design was applied with four replications. Potential grain yield is highly affected by the number of reproductive tillers; differences in final grain yield were highly and positively correlated to the number of tillers (r= 0.54**) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Urea with 46% nitrogen was used as the fertilizer, and it was given in three batches during the stages of planting, tillering, and stem elongation at a rate of 200 kg ha-1. Contrarily, a plot of land received 120 kg of triple super phosphate fertilizer (46% P2O5) before the soil started to soften (11). The experimental units were irrigated whenever needed, and crop service operations were carried out according to the recommendations followed.…”
Section: Methodsmentioning
confidence: 99%
“…Urea with 46% nitrogen was used as the fertilizer, and it was given in three batches during the stages of planting, tillering, and stem elongation at a rate of 200 kg ha-1. Contrarily, a plot of land received 120 kg of triple super phosphate fertilizer (46% P2O5) before the soil started to soften (11). The experimental units were irrigated whenever needed, and crop service operations were carried out according to the recommendations followed.…”
Section: Methodsmentioning
confidence: 99%
“…Finally; the 1000-kernal weight was 28.20 [16], 33.56 [14], 34.60 [21] , 34.70 [19], 35.10 [15] , 35.80 [22], 38.00 [18], 39.60 [23], 42,10 [24] , and 43.89 [25], for the Abu-Ghraib3 varieties. The grain weights were assigned to the same verity under different conditions [26] .Another study revealed that the 1000kernel weight was 33.5 [16]. Three other varieties showed different 1000-kernel weights, Rasheed 41.61, Bohooth 22 38.20; and Bohooth was, 35.83 [27].…”
Section: Grain Weightmentioning
confidence: 99%